KRETERIA KHUSUS YANG HARUS DIPENUHI GHARIM DALAM AL-QURAN SURAT AT-TAUBAH AYAT 60 STUDI TAFSIR IBNU KATSIR - Andriantoro; Haslinda; Chalid Sitorus (ejournal.nurulqadim.ac.id, 2025)
This study aims to describe the specific criteria that must be fulfilled by a gharim (debtor) as mentioned in the Qur'an, Surah At-Tawbah verse 60, based on the interpretation of Ibn Kathir. The data collection method used in this study is qualitative research with a library research approach. The data were collected by examining literature, documents, and other sources of information related to the research topic. The findings of this study are as follows: First, according to Ibn Kathir’s interpretation, a gharim in Surah At-Tawbah verse 60 refers to individuals who are in debt due to economic hardship and are unable to meet their basic needs. The qualifying types of debt include: inability to repay, lawful (halal) debts, and debts incurred for essential needs. Conversely, certain debts are disqualified, such as those resulting from sinful acts like interest (usury), gambling, or online gambling. Ibn Kathir emphasizes the importance of ensuring that the debt is lawful. Second, the specific criteria that must be met by a gharim include: the debt is due and must be repaid immediately, the debt was not incurred for non-essential consumption, and the debt was taken for fundamental needs or public benefit. Third, giving zakat to a gharim who does not meet these criteria may lead to misuse and ineffectiveness in assisting those truly in need. A person is not eligible to receive zakat for debt repayment if they possess savings or assets that could be used to settle the debt.